2014
DOI: 10.1007/s11664-014-3314-z
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Analysis of Thermoelectric Modules Under Constant Heat Flux

Abstract: Thermoelectric power generation (TEG) is examined in case of the radiation heating.A constant heat flux is assumed in addition to the consideration of Seebeck effect, Peltier effect and Joule heat with the temperature dependencies of materials' properties.Numerical evaluations are conducted using combination of the finite-volume method (FVM) and an original simultaneous solver among the heat transfer, thermoelectric and electric transportation phenomena. The comparison with the experimental results shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In these cases, the final hot and cold temperatures and the corresponding temperature gradient through the device depend on the heat flux, the cooling capacity of the cold end, and the heat losses. Some analytical and numerical approaches can be found under these constraints for bulk thermoelectric generators in previous works …”
Section: Efficiency and Output Power Calculated Values Of Tgsmentioning
confidence: 99%
“…In these cases, the final hot and cold temperatures and the corresponding temperature gradient through the device depend on the heat flux, the cooling capacity of the cold end, and the heat losses. Some analytical and numerical approaches can be found under these constraints for bulk thermoelectric generators in previous works …”
Section: Efficiency and Output Power Calculated Values Of Tgsmentioning
confidence: 99%
“…For instance, studies on TEGs for waste heat recovery have shown a strong influence of heat exchanger parameters such as channel width, channel height, fin type, fin density, and fin thickness along with convective, conductive, and contact thermal resistances. , TEG performance for body energy harvesting has been found to be dictated by internal thermal resistance, which must be high and comparable to the parasitic thermal resistances in series with the TEG. Thermal resistance/impedance matching studies have shown that maximum TEG power is obtained when the temperature drop across the module is nearly equal to half of the temperature difference between heat source and heat sink. , Systematic assessment of TEG for solar energy harvesting and other radiant heat recovery systems requires a different analytical approach than the traditional modeling, where TEGs are usually subjected to a constant temperature condition. Under the constant heat flux condition, the hot-side temperature is not fixed but depends on the inward heat flux and the heat transfer capacity at the cold-side. …”
Section: Introductionmentioning
confidence: 99%
“…Our previous works discussed the basic TE phenomenon under constant thermal conditions for various module designs, i.e. fixed the temperature or the heat flux on hot and cold surfaces and analyzed TE performance of the helical and conventional straight panels, as well as modules consisting of tilted parallelogram-and polyhedron-shaped thermo-elements [5][6][7][8][9] . However, the most likely approach to utilize the residual heat of waste fluids is to allow the high-temperature gas and liquid to flow on module surfaces.…”
Section: Introductionmentioning
confidence: 99%